Taxonomy and physiology of lactic acid bacteria from fortified and natural wines - Loubser, P. A.(Petrus Abel) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1993.